Developmental windows and environment as important factors in the expression of genetic information: a cardiovascular physiologist's view - Kunes, Jaroslav; Zicha, Josef (Clinical science (London, England, 2006)
Genetic studies in humans and rodent models should help to identify altered genes important in the development of cardiovascular diseases, such as hypertension. Despite the considerable research effort, it is still difficult to identify all of the genes involved in altered blood pressure regulation thereby leading to essential hypertension. We should keep in mind that genetic hypertension and other cardiovascular diseases might develop as a consequence of early errors in well-co-ordinated systems regulating cardiovascular homoeostasis. If these early abnormalities in the ontogenetic cascade of expression of genetic information occur in critical periods of development (developmental windows), they can adversely modify subsequent development of the cardiovascular system. The consideration that hypertension and/or other cardiovascular diseases are late consequences of abnormal ontogeny of the cardiovascular system could explain why so many complex interactions among genes and environmental factors play such a significant role in the pathogenesis of these diseases. The detailed description and precise time resolution of major developmental events occurring during particular stages of ontogeny in healthy individuals (including advanced knowledge of gene expression) could facilitate the detection of abnormalities crucial for the development of cardiovascular alterations characteristic of the respective diseases. Transient gene switch-on or switch-off in specific developmental windows might be a useful approach for in vivo modelling of pathological processes. This should help to elucidate the mechanisms underlying cardiovascular diseases (including hypertension) and to develop strategies to prevent the development of such diseases.
Keywords: rizikové faktory; Environment; kardiovaskulární nemoci; Animals; životní prostředí; Risk Factors; věkové faktory; lidé; hypertenze; zvířata; Hypertension; Cardiovascular Diseases; vývojová regulace genové exprese; Age Factors; Gene Expression Regulation, Developmental; Humans